Transketolase activity modulates glycerol‐3‐phosphate levels in Escherichia coli. Issue 2 (1st March 2016) - Vimala, A.; Harinarayanan, R.
Summary: Transketolase activity provides an important link between the metabolic pathways of glycolysis and pentose phosphate shunt and catalyzes inter‐conversions between pentose phosphates and glycolytic intermediates. It is widely conserved in life forms. A genetic screen for suppression of the growth defect of Escherichia coli tktA tktB mutant in LB medium revealed two mutations, one that rendered the glpK expression constitutive and another that inactivated deoB . Characterizing these mutations aided in uncovering the role of ribose‐5‐P (a transketolase substrate) as an inhibitor of glycerol assimilation and de novo glycerol‐3‐P synthesis. Using lacZ fusions, we show that ribose‐5‐P enhances GlpR–mediated repression of the glpFKX operon and inhibits glycerol assimilation. Electrophoretic Mobility Shift Assay (EMSA) showed ribose‐5‐P made the DNA‐GlpR complex less sensitive to the inducer glycerol‐3‐P. In addition to inhibition of glycerol assimilation, obstruction of ribose‐5‐P metabolism retards growth from glycerol‐3‐P limitation. Glucose helps to overcome this limitation through a mechanism involving catabolite repression. To our knowledge, this report is the first to show ribose‐5‐P can modulate glycerol‐3‐P concentration in the cell by regulation of glycerol assimilation as well as its de novo synthesis. This regulation could be prevalent in other organisms. Abstract : A schematic depiction of negative regulation of glycerol metabolism by ribose‐5‐P through GlpR the repressor of glp regulon.